What Are the Sociodemographic and Clinical Characteristics and Needs of Mothers Who Access Acute Postpartum Psychiatric Care and Have Children's Social Care Involvement?. (11th February 2023) - Lever Taylor, Billie; Brobbey, Latoya; Howard, Louise M.; Masters, Brooklynn; Molloy, Zara; Potts, Laura C.; Powell, Claire; Stanley, Nicky; Trevillion, Kylee; Sweeney, Angela
Abstract : Mothers with severe postpartum psychiatric diagnoses are more likely to have children's social care involvement with their infants, but little is known about the needs or experiences of this group of women. With input from a lived experience advisory group, we carried out secondary analysis of data collected from 278 mother-infant dyads where the mother accessed acute psychiatric care in England or Wales postnatally. We explored the characteristics, needs, and service use experiences of mother-infant dyads with ( n = 99) and without ( n = 179) children's social care involvement. We found that mothers with social care involvement were often experiencing wider adversity and inequity across multiple areas of their lives. These mothers were also less satisfied with their mental health care and had more unmet needs after discharge from acute services. We built multivariable logistic regression models to examine factors associated with children's social care involvement during the acute admission and one year later. We found that having social care involvement during an acute postpartum admission was associated with being deprived, reporting a maternal history of childhood trauma, experiencing domestic abuse, having a diagnosis of personality disorder or schizophrenia, and having a history of previous psychiatric admissions. At one-year follow-up, factors associated with children's social care involvement included deprivation, experiencing childhood trauma, having been single at the time of the postpartum admission, and having been readmitted to acute psychiatric services following the postpartum admission. Our findings suggest that mothers with children's social services involvement in the context of an acute postpartum psychiatric diagnosis may have high levels of support needs, but services may struggle to meet their needs fully. We argue that an increased focus on supporting mothers with histories of trauma, adversity, and deprivation, along with greater collaboration between mental health, children's social care, and third sector services may help improve experiences and outcomes.